A Comparative Study on Local Governments’ Institutional Capacity of Service Delivery in Bhojpur (Intellectual Inception: A Multidisciplinary Research Journal of Bhojpur Campus, 2024)
This study is a comparison of Local Governments' Institutional Capacity Self-Assessment (LISA) scores on service delivery of local governments in Bhojpur district during four fiscal years.  The principal objective is to compare and analyze the LISA scores and find out the status on service delivery area of local governments in Bhojpur district. It has focused on comparative analysis of the status of local governments using their self-assessment scores to find out the progress in service delivery of local government institutions. The methodology used in this study is collecting secondary data of self-assessment reports from the website, and compare and analyze the data of all local governments over the four fiscal years. This study has followed descriptive and analytical approach as well as used document review, and website observation as research tools. Data collection has been done from secondary sources of data. The finding of this study reveals that the service delivery status of local governments has been gradually increased in LISA scores over the period. The emphasis on service delivery during the self-assessment has been given most and provided largest weightage and most indicators included. The Bhojpur municipality, where headquarter of the district located has been evaluated less scores than another municipality and the far remote rural municipalities, such as Salpa Silichho and Amchowk rural municipalities.